Bhāratīẏa darśana kosha - Bhaṭṭācārya, Śrīmohana (Kalikātā Saṃskrta Mahābidyālaẏa gabeshaṇā granthamālā ; granthāṅka 117, 121 : Lexicon ; no. 5, 7., 1978)
Encyclopaedic dictionary of technical terms used in all branches of Indian philosophy.